Peranan Tadbir Urus Kolaboratif Melalui Kumpulan Dasa Wisma dalam Meningkatkan Kualiti Hidup Masyarakat Masa Pandemik Covid-19 di Kabupaten Bintan - Usman Siam, Nurbaiti; Bagus Prastiyo, Endri (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
The Covid-19 pandemic has had a huge social impact on people's lives, one of the most affected is economic problems, so people have to adjust to a situation full of uncertainty like today. This study aims to look at the role of collaborative tadbir urus run by Dasawisma in improving food security for the community amid the Covid-19 pandemic. In this study the investigators took one Dasa Wisma object, namely Dasa Wisma Kenanga in Bintan Regency as a community forum to carry out agricultural activities in an effort to fulfill their daily needs. In obtaining this data, this study uses qualitative research methods, using observation, interview, and documentation collection techniques. The results of this study explain the role of Dasa Wisma in improving food security during the pandemic in Bintan Regency as well as several work programs that have been carried out by this farmer group which are very helpful and beneficial to the community, besides being able to meet the needs of food produced by their group can also be sold to help the family economy. The results of the study also show that this farmer group was indeed formed before the Covid-19 pandemic, but when this pandemic appeared and damaged the economy, members of this farmer group had the availability to meet their daily needs.